(untitled) (Studia Prawnicze / The Legal Studies, 2020)
W artykule podjęto próbę ustalenia, czy koncepcja etyczna J. Benthama może służyć jako teoretyczne uzasadnienie dla ustawowej dereifikacji zwierząt. Autor ten dostrzegał związek przyczynowy zachodzący pomiędzy okrucieństwem wobec zwierząt, a uznaniem ich w systematyce prawa za rzecz. Prawdziwość tej tezy budzi jednak wątpliwości. Obowiązek humanitarnego traktowania zwierząt zawarty w ustawie nie jest wynikiem uznania, że zwierzę nie jest rzeczą. Prowadzi to do wniosku, że ustawowa dereifikacja zwierząt jest nie tyle koncepcją prawną, co ideologiczną. O ile sama w sobie nie poprawia ona losu zwierząt, to na płaszczyźnie prawnej otwiera drzwi dla przyznania zwierzętom podmiotowości, a w przyszłości nawet praw podmiotowych. The article examines the question of whether J. Bentham’s ethical theory can serve as a theoretical justification for the statutory dereification of animals. This author saw a causal connection between cruelty to animals and classifying them as a thing (res) in law. The correctness of this conclusion appears debatable, however. The obligation to treat animals in a humane manner is not connected to and, in particular, does not issue from a statutory declaration that an animal is not a thing. This leads to the conclusion that statutory dereification is an ideological concept rather than a legal one. While by itself it does not improve the situation of animals, it nevertheless, in a legal perspective, opens the door to recognizing them as subjects of law, and, in the future, possibly to granting them rights.